Daya Tarik Shopee : Pengaruh Harga dan Voucher terhadap Keputusan Pembelian di Shopee (Jurnal Manajemen Kreatif dan Inovasi, 2025)
This study aims to examine whether price and vouchers influence the purchasing decisions of Economics Education student at Universitas Sebelas Maret on the e-commerce platform Shopee. Forty-five respondent who had previously shopeed on Shopee were given questionnaires as part of quantitative approach and causality study methodology. Multiple linear regression analysis, validity, reliability, and classical assumption test were used to analyze the data. The regression coefficients for price (0,434) and vouchers (0,330) indicate that both price and vouchers have a positive and significant impact on purchasing decisions. Based on the F test, these two factors collectively contribute 55% to purchasing decisions. These results highlight the importance of pricing strategies and vouchers in inflluencing Shopee customers shopping decisions. To make findings more generalizable and comprehensive, future reasearch is recomended to increase the number of respondents and incorporate additional variables, such as aspects related to product quality, service, or promotions